Oxytocin and excitation/inhibition balance in social recognition. (December 2018) - Lopatina, Olga L.; Komleva, Yulia K.; Gorina, Yana V.; Olovyannikova, Raisa Ya; Trufanova, Lyudmila V.; Hashimoto, Takanori; Takahashi, Tetsuya; Kikuchi, Mitsuru; Minabe, Yoshio; Higashida, Haruhiro; Salmina, Alla B.
Abstract: Social recognition is the sensitive domains of complex behavior critical for identification, interpretation and storage of socially meaningful information. Social recognition develops throughout childhood and adolescent, and is affected in a wide variety of psychiatric disorders. Recently, new data appeared on the molecular mechanisms of these processes, particularly, the excitatory–inhibitory (E/I) ratio which is modified during development, and then E/I balance is established in the adult brain. While E/I imbalance has been proposed as a mechanism for schizophrenia, it also seems to be the common mechanism in autism spectrum disorder (ASD). In addition, there is a strong suggestion that the oxytocinergic system is related to GABA-mediated E/I control in the context of brain socialization. In this review, we attempt to summarize the underpinning molecular mechanisms of E/I balance and its imbalance, and related biomarkers in the brain in healthiness and pathology. In addition, because there are increasing interest on oxytocin in the social neuroscience field, we will pay intensive attention to the role of oxytocin in maintaining E/I balance from the viewpoint of its effects on improving social impairment in psychiatric diseases, especially in ASD. Highlights: Social cognitive information is controlled by E/I balance in defined brain systems. Neuropsychiatric diseases are characterized by impaired E/I balance. Markers of E/I balance are useful for monitoring neurodevelopmental alterations. Oxytocin regulates E/I balance from the very early stages of brain development. Lack of oxytocin leads to impaired E/I balance and altered social recognition.